Spatiotemporally controlled generation of NTPs for single-molecule studies of NTP-driven processes - Sabantcev, Anton; Mao, Guanzhong; Aguirre Rivera, Javier; Panfilov, Mikhail; Arseniev, Anatolii; Ho, Oanh; Khodorkovskiy, Mikhail A.; Deindl, Sebastian (Uppsala University, 2022)
Data supporting the findings of the paper titled "Spatiotemporally controlled generation of NTPs for single-molecule studies" in Nature Chemical Biology which describes a method for controlling NTP-driven reactions in single-molecule experiments via the local generation of NTPs (LAGOON) that increases the measurement throughput and enables single-turnover observations.

The dataset contains single-molecule FRET data capturing T4 helicase DNA unwinding, nucleosome remodeling by Chd1 and the invasion of a nucleosome by the T7 RNA polymerase. Additionally, the dataset contains acoustic force spectroscopy data on E. coli RNA polymerase elongation.
Keywords: Enzymes; Biochemistry and cell biology not elsewhere classified; Medical and Health Sciences; Medicin och hälsovetenskap; Biochemistry; Biokemi